2021
DOI: 10.1515/bot-2021-0027
|View full text |Cite
|
Sign up to set email alerts
|

Trace element concentrations in seaweeds of the Arabian Gulf identified by morphology and DNA barcodes

Abstract: Even though seaweeds have been considered a nutrient-rich dietary source of minerals in other parts of the world, there is little knowledge about trace element accumulation in seaweeds of the Arabian Gulf. The Arabian Gulf is of particular interest due to being an extreme environment, as it features some of the highest temperatures and salinities observed in any marine waters in the world. This study determined the minerals contents using inductively-coupled plasma-mass spectrometry (ICP-MS) in 10 of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, Ulva spp. are not only rich in essential PUFAs, but also contain high amounts of macroand micronutrients as reported previously [71]. In addition, the nutritional value of Ulva species in terms of carbohydrates, protein, and fatty acids (especially PUFA content) has been reported to be comparable to some vegetables, nuts, and grains [2,23,72] and it has been consumed traditionally for centuries in many Asian countries [1,2,4,25,72].…”
Section: Nutritional Assessment For Seaweed Valorizationmentioning
confidence: 61%
“…Nevertheless, Ulva spp. are not only rich in essential PUFAs, but also contain high amounts of macroand micronutrients as reported previously [71]. In addition, the nutritional value of Ulva species in terms of carbohydrates, protein, and fatty acids (especially PUFA content) has been reported to be comparable to some vegetables, nuts, and grains [2,23,72] and it has been consumed traditionally for centuries in many Asian countries [1,2,4,25,72].…”
Section: Nutritional Assessment For Seaweed Valorizationmentioning
confidence: 61%
“…However, in Kuwait only eight publications mention members of the Sargassaceae: along members of the genera Hormophysa, Polycladia, and Sirophysalis, ten species of Sargassum have been reported (Jones, 1986;Al-Hasan, Jones, 1989;John, Al-Thani, 2014;Al-Yamani et al, 2014;Alghunaim et al, 2019aAlghunaim et al, , b, 2020. Most recently, two papers have explored concentrations of iodine and fluorine (Al-Adilah et al, 2020) and other trace elements (Al-Adilah et al, 2021) in Sargassum species from Kuwait. These papers were the first to report any nucleotide sequence data for Sargassum species from the Gulf.…”
Section: Introductionmentioning
confidence: 99%
“…Macroalgae, particularly brown, are a part of the main diet of many countries (Dawczynski, Schubert, & Jahreis, 2007;Miyashita et al, 2012;Muradian, Vaiserman, Min, & Fraifeld, 2015), and different ratios of polysaccharides, antioxidants, vitamins, minerals, proteins, and lipids that contain (Schmid et al, 2018;Nunes, Valente, Ferraz, Barreto, & Carvalho, 2020;Al-Adilah et al, 2021). In addition, it has been suggested that brown seaweeds have great amounts of PUFA, which are not present in land plants (Kumari, Bijo, Mantri, Reddy, & Jha, 2013;Polat & Ozogul, 2013;Schmid et al, 2018;Al-Adilah et al, 2021). Seaweeds have contained a significant amount of essential fatty acids, despite the low lipid concentration (Rocha et al, 2021), they can be used as an alternative to a marine lipid resource due to browns seaweeds abundance among coastal algae (Airanthi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%